PENINGKATAN KEAKTIFAN BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) PADA SISWA KELAS IV DI SDN 001 BANGKINANG - Sri Wahyuningsih; Ramdhan Witarsa; Rizki Ananda (Jurnal Muassis Pendidikan Dasar, 2022)
This research is motivated by the low learning activity of fourth grade students at SDN 001 Bangkinang. One solution to overcome this problem is to use the Student Team Achievement Division (STAD) type of cooperative learning model. The purpose of this study was to describe the increase in student activeness in Class IV SDN 001 Bangkinang. This research method is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, and reflection. The time of the study was carried out from August to September 2021. The subjects of this research were 17 grade IV students, with 8 male students and 9 female students. The collection technique is in the form of documentation, and observation. The results of this study indicate that the learning activity of fourth graders at SDN 001 Bangkinang in the classical completeness pre-action reached 35.29% with an average score of 64,36 criteria (CA), in the first cycle of the first meeting it reached 41.17% with an average score. 68,73 criteria (CA), in the second meeting it increased to 52.94% with an average value of 71,93 criteria (A). In cycle 2, the first meeting increased to 64.70% with an average value of 75,96 criteria (A), in the second meeting it increased to 76.47% with an average value of 80,00 criteria (A). It was concluded that using the Student Team Achievement Division (STAD) type cooperative learning model could increase the learning activity of fourth graders at SDN 001 Bangkinang